Instructional writing in English : studies in honour of Risto Hiltunen - Peikola, Matti; Skaffari, Janne; Tanskanen, Sanna-Kaisa; Hiltunen, Risto (Pragmatics & beyond, 2009)
The history of English writing is, to a considerable extent, the history of instructional writing in English. This volume is the first collection of papers to focus on instructional writing throughout the history of the language. Spanning a millennium of English texts, the materials studied represent procedural and behavioural discourse in a variety of genres. The primary texts, from Ælfric's homilies to medieval cooking recipes to seventeenth-century American conduct literature to present-day language textbooks, display a variety of linguistic devices typical of instruction. The materials non.